The outsider - Wright, Richard, 1908-1960. (New York : Harper Perennial, 2008)
[The author] presents a compelling story of a black man's attempt to escape his past and start anew in Harlem. Cross Damon is a man at odds with society and with himself, a man who hungers for peace but who brings terror and destruction wherever he goes.
Dread -- Dream -- Descent -- Despair -- Decision -- Chronology.
"The restored text established by the Library of America."
Keywords: African American men -- Fiction; Alienation (Social psychology) -- Fiction; False personation -- Fiction; Communists -- Fiction; Murderers -- Fiction; Racism -- Fiction; Psychological fiction